Kemampuan Higher Order Thinking Skill Melalui Model Contextual Teaching and Learning Berdiferensiasi - Ai Halimatus Salamah; Jujun Ratnasari; Setiono Setiono (Universitas Majalengka, 2023)
Abstrack The research conducted was motivated by the demands of the school curriculum in improving learning with students who had difficulty doing HOTS questions, so that students' HOTS abilities were still low. This study aims to determine the ability to think higher order (hots) in CTL is distinguished by looking at the increase in students' higher order thinking skills (hots) based on student learning styles. The method used in this study is quantitative descriptive. The subjects of the study were 30 students of SMP Negeri 1 Kota Sukabumi. The sampling technique used is purposive sampling using the Multiple Choice HOTS test instrument. The results showed that the percentage of students' HOTS ability averaged 72.87 ± 18.26% with good criteria, with the average pretest and posttest results of the linguistic learning group were 43.37 ± 8.34% and postest 70.89 ± 6.29 %. While in the visual-auditory learning style, the pretest value was 43.64 19.10%, and the postest value was 78.64 ± 9.33%. Furthermore, the percentage of N-gain scores on the ability of HOTS students in the linguistic and visual-auditory learning groups was in the medium category, namely in the linguistic learning group with a value of 0.48 and in visual-auditory learning got a value of 0.62. Therefore, learning using the CTL model is well differentiated to improve HOTS seen from the increase in the percentage of HOTS ability and N-Gain value of each linguistic and visual-auditory learning style group, with the highest value obtained by the visual-auditory group. Thus, the HOTS ability of the visual-auditory group is superior to the HOTS ability of the linguistic learning group. Abstrak Penelitian yang dilakukan dilatar belakangi oleh tuntutan kurikulum sekolah dalam meningkatkan pembelajaran dengan siswa yang kesulitan mengerjakan soal HOTS, sehingga kemampuan HOTS siswa masih rendah. Tujuan penelitian ini adalah mengetahui kemampuan berpikir tingkat tinggi (hots) melalui model belajar CTL dibedakan melalui peningkatan kemampuan berpikir tingkat tinggi (hots) siswa berdasarkan kebutuhannya. Metode yang digunakan dalam penelitian ini adalah deskriptif kuantitatif. Subyek penelitian adalah siswa SMP Negeri 1 Kota Sukabumi yang berjumlah 30 siswa. Teknik pengambilan sampel adalah purposive sampling menggunakan instrumen tes HOTS Pilihan Ganda. Hasil penelitian menunjukkan persentase kemampuan HOTS siswa rata-rata 72,87 ± 18,26% dengan kriteria baik, dengan rata-rata hasil pretest dan posttest kelompok pembelajaran linguistik adalah 43,37 ± 8,34% dan postest 70,89 ± 6,29%. Sedangkan pada gaya belajar visual-auditory nilai pretest 43,64 19,10%, dan nilai postest 78,64 ± 9,33%. Selanjutnya persentase skor N-Gain pada kemampuan HOTS siswa kelompok pembelajaran linguistik dan visual-auditory berada pada kategori sedang yaitu pada kelompok pembelajaran linguistik dengan nilai 0,48 dan pada pembelajaran visual-auditory mendapat nilai 0,62. Oleh karena itu, pembelajaran melalui model CTL berdiferensiasi baik untuk meningkatkan kemampuan HOTS dilihat dari kenaikan persentase kemampuan HOTS dan nilai N-Gain setiap kelompok gaya belajar linguistik dan visual-auditory, dengan nilai tertinggi diperoleh oleh kelompok visual-auditory. Sehingga, kemampuan HOTS kelompok visual-auditory lebih unggul dibandingkan kemampuan HOTS kelompok belajar linguistik.